BLOOM OF TRICHODESMIUM THIEBAUTII GOMONT IN THE GULF OF MANNAR AT MANDAPAM - James, P S B R (Indian Journal of Fisheries, 2011)
A bloom of the blue-green alga, Trichodesmium thiebautii, was observed during the last week of May 1968 in the Gulf of Mannar along the Mandapam Coast. The alga was found in abundance in various stages of disintegration in the glass tanks of the sea-water aquarium of the Central Marine Fisheries Research Institute, Mandapam Camp, which caused mortality of fishes kept for experimental purposes. However, no fish mortality was reported from the sea